PERANCANGAN SMART VERTICAL GARDEN SEBAGAI STRATEGI MENINGKATKAN RUANG HIJAU DAN KENYAMANAN TERMAL: DESIGNING SMART VERTICAL GARDENS AS A STRATEGY TO ENHANCE GREEN SPACES AND THERMAL COMFORT - Andi Sahputra Depari; Hijriah; Umar Mustofa; Sisilia Faradita Rumengan; Donalia; Mallika Putri Santoso (Universitas Trisakti, 2024)
Balikpapan, located in East Kalimantan Province, Indonesia, is experiencing rapid growth accompanied by increasingly complex environmental challenges, including the effects of climate change. Data shows a rise in air temperature, impacting not only the outdoor environment but also the indoor thermal conditions of public buildings such as offices, shopping centers, and educational institutions. At Institut Teknologi Kalimantan (ITK), the increasing demand for air conditioning systems reflects the direct impact of global temperature rise, resulting in heightened energy use and greenhouse gas emissions. In response to these issues, this research explores the design and implementation of smart vertical gardens as an innovative solution to enhance thermal comfort and energy efficiency. The smart vertical garden utilizes shading plants, sensor technology, and automation to reduce a building’s carbon footprint while improving thermal comfort. Building B at ITK is chosen as the case study due to its function as a hub of academic activities, making it a strategic location for implementing this green technology. The research adopts a comprehensive approach, including literature review, empirical data collection, thermal analysis, simulation, and design. The findings demonstrate the effectiveness of the smart vertical garden in reducing cooling energy demand, improving thermal comfort, and promoting campus greening. The implementation of this technology has the potential to serve as a sustainability model for public buildings. The results of this study provide valuable insights for academics, practitioners, and policymakers in developing green strategies and advancing sustainable development.